2017
DOI: 10.1093/protein/gzx004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the molecular mechanism of substrate channeling and domain communication in protozoal bifunctional TS-DHFR

Abstract: Most species, such as humans, have monofunctional forms of thymidylate synthase (TS) and dihydrofolate reductase (DHFR) that are key folate metabolism enzymes making critical folate components required for DNA synthesis. In contrast, several parasitic protozoa, including Leishmania major (Lm), Plasmodium falciparum (Pf), Toxoplasma gondii (Tg) and Cryptosporidium hominis (Ch), contain a unique bifunctional thymidylate synthase-dihydrofolate reductase (TS-DHFR) having the two sequential catalytic activities con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The two active sites are about 40 Å apart, separated by a solvent‐exposed tunnel. This tunnel is lined by an excess of positively charged residues , suggesting that substrate channeling of the negatively charged acyl‐CoA molecules via electrostatic interactions with the positively charged tunnel surface could be important, as described for the thymidylate synthase–dihydrofolate reductase bifunctional enzyme .…”
mentioning
confidence: 91%
“…The two active sites are about 40 Å apart, separated by a solvent‐exposed tunnel. This tunnel is lined by an excess of positively charged residues , suggesting that substrate channeling of the negatively charged acyl‐CoA molecules via electrostatic interactions with the positively charged tunnel surface could be important, as described for the thymidylate synthase–dihydrofolate reductase bifunctional enzyme .…”
mentioning
confidence: 91%
“…Thymidylate synthase (TS, UniProt entry P0A884) is a dimeric enzyme responsible for the synthesis of the sole de novo source of deoxythymidine monophosphate (dTMP) in most organisms. Some pathogenic microbes utilize two forms of TS, one canonical thy A type and the other a flavin-dependent enzyme, or thy X, type. , In addition, although some organisms use so-called bifunctional enzymes, where TS and another enzyme in the folate metabolism cycle, dihydrofolate reductase, are encoded on the same polypeptide, the fold and primary sequences of thy A-type TS enzymes are highly conserved in all forms studied to date. TS uses a multiple-step reaction coordinate along which both a methylene and hydride are donated from the methylene tetrahydrofolate (mTHF) cofactor to the deoxyuridine monophosphate (dUMP) substrate.…”
mentioning
confidence: 99%
“…Active sites of DHFR and TS are located on different faces of the TgDHFR-TS structure like other apicomplexan DHFR-TS enzymes. The JR between DHFR and TS moieties in apicomplexans is rather long (55–91 amino acids), whereas it is much shorter or absent in other kinetoplastids such as Trypanosoma brucei, Trypanosoma cruzi, and Leishmania major . It is reported that the JR is essential for the catalytic activity of Pf-, Ch-, and Tg-DHFR-TS enzymes. ,, A crossover helix in JR is found in all apicomplexan enzymes with various lengths.…”
Section: Resultsmentioning
confidence: 99%